2016
DOI: 10.1016/j.memsci.2016.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Optimal backwashing in dead-end bacterial microfiltration with irreversible attachment mediated by extracellular polymeric substances production

Abstract: Microfiltration and ultrafiltration are methods of removing colloidal impurities from water and wastewater. One of the major issues when dealing with the practical implementation of membranes is the reduction of water productivity as the foulants accumulate on the membrane surface or within the pores. Membrane regeneration by periodic backwashing is an effective method of reducing fouling; however, to date the timing and duration of the backwashing for effective fouling control is largely only empirically dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…Apparently, quick formation of a cake layer hindered effective removal of bacteria, because only 49% reduction in the reactors initial bacterial population was observed ( Figure 4a). As there are minimal changes in the turbidity of the permeate (Figure 4a), the reported decrease in bacteria concentration in the main reactor must probably be attributed to the attachment/deposition of bacterial cake on the membrane surface [33,34].…”
Section: The Effect Of Dilution Rate Backwash and Membrane Surface Amentioning
confidence: 93%
See 1 more Smart Citation
“…Apparently, quick formation of a cake layer hindered effective removal of bacteria, because only 49% reduction in the reactors initial bacterial population was observed ( Figure 4a). As there are minimal changes in the turbidity of the permeate (Figure 4a), the reported decrease in bacteria concentration in the main reactor must probably be attributed to the attachment/deposition of bacterial cake on the membrane surface [33,34].…”
Section: The Effect Of Dilution Rate Backwash and Membrane Surface Amentioning
confidence: 93%
“…The surface condition of an immersed membrane directly affects its filtration capability [25]. In order to keep the membrane surface clean and prevent fouling, backwashing is an effective physical cleaning remedy [34]. Hence, 2 different backwashing regimes were applied: 3.5 min forward flow, and 0.5 min backwash (4 min cycle) at a dilution rate 0.5 1/h (109 L/h·m 2 ), and a more frequent backwash of 2.5 min forward flow plus 0.5 min backwash (3 min cycle) at a higher dilution rate of 0.66 1/h (144 L/h·m 2 ).…”
Section: The Effect Of Dilution Rate Backwash and Membrane Surface Amentioning
confidence: 99%
“…Assuming that R c is formed at the same pressure, when comparing the mass of foulants accumulated on the membrane surface, R c can be determined by Equation (3) [17][18][19], where α is the specific cake resistance, C b is the mass of dry cake solids per volume of filtrate, V is the cumulative permeate quantity, and A is the effective membrane surface area.…”
Section: Measurement Fouling Mechanismsmentioning
confidence: 99%
“…An application on a case study showed that the optimal strategy allows for significant gains in operating time and consumption of thinner in comparison with a conventional strategy of operation. Cogan et al (2016) applied the Pontryagin Maximum principle to predict the optimal times of switching between periods of filtration and backwashing that maximize the net production of water over a running time given a membrane filtration process. The authors adopted a specific model published in the literature describing the dynamics of the ultrafiltration/microfiltration reaching promising results.…”
Section: Closed-loop Controlmentioning
confidence: 99%